MATERI, METODE, DAN EVALUASI PEMBELAJARAN DALAM PERSPEKTIF AL-QUR’AN - subur subur (IAIN Purwokerto, 2015)
Abstract: Mahmoud Syalthut said that al-Qur'an mulÄimun fiullizzamn walmakn (al-Quran always relevant to space and time), in the Koran, there are also many verses that contain concepts and values education, material and methodology. Therefore, this study was conducted to determine the concepts of the Koran relating to the scope of materials, methods, and evaluation of leaming and its relevance to the existing concept. Source of this research is a document, using thematic followed by reflective, inductive, and language analysis. The results showed that the leaming material in the Koran, which is divided into material and non-Syariyah Syariyah. Syariyah divided into theology, Sharn'ah, and morals. Non-Syariyah material divided into exact and the humanities. Leaming methods can be traced in the Qur'an among hiwar, story, amtsal, exemplary, habituation, ibrah-mauidzah, targhib-tarhib, advice, persuasion/wisdom, tsawab-igab, lecture, question and answer, discussion, sorogan, bandongan, mudzakarah, assignments, field tnips, experiments, dril, sociodrama, demonstrations and group work. The leaming activities in the form of Darasa, Nazara, ltibr, tafakkur, tazakkur, tadabbur, Iqro, 'agala, rabbaya. Keywords: Materials, Methods, Evaluation, Leaming, Quran.